2004
DOI: 10.2169/internalmedicine.43.436
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid Fever as a Rare Cause of Hepatic, Splenic, and Bone Marrow Granulomas

Abstract: During the course of typhoid fever, the usual histologic finding of the liver is "nonspecific reactive hepatitis." Hepatic granuloma (HG) is a rare complication of typhoid fever. We present two cases of typhoid fever with HG and review the relevant literature. Case 1 (a 53-yearold female) was found to have both hepatic and splenic granulomas. This is the first case of typhoid fever with splenic granulomas in the English language literature. Case 2 (a 66-year-old male) developed granulomas in the bone marrow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 15 publications
2
23
1
Order By: Relevance
“…In differential diagnosis with acute viral infections, the severity of jaundice and the extent of elevation of transaminase levels are much greater than those observed in typhoid fever. The cause of the increase in transaminases in typhoid fever may also be hepatic granulomas or hepatic abscesses formation (14). But in our case, there was no such a space-occupying lesion.…”
Section: Discussioncontrasting
confidence: 48%
“…In differential diagnosis with acute viral infections, the severity of jaundice and the extent of elevation of transaminase levels are much greater than those observed in typhoid fever. The cause of the increase in transaminases in typhoid fever may also be hepatic granulomas or hepatic abscesses formation (14). But in our case, there was no such a space-occupying lesion.…”
Section: Discussioncontrasting
confidence: 48%
“…The patient improved rapidly with the treatment of typhoid fever. Mert et al [4] also reported a case with splenic granuloma and another case with bone marrow granuloma in addition to hepatic granuloma.…”
Section: Discussionmentioning
confidence: 96%
“…When it occurs, granulomas are described in sites other than the primary intestinal ulcer. Only 5 cases of typhoid fever with hepatic granulomas have been reported in the English language literature [2][3][4] . Paris [2] reported 5 cases of typhoid hepatitis, out of which 2 revealed hepatic granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Re ports of granulomas in the liver, bone marrow and spleen with typhoid fever have been published previously. 8 An account of cutaneous granulomata associated with the typhoid -paratyphoid heat-killed vaccine has also been reported. 9 Previously reported histopathologic findings associated with typhoid enteritis include hypertrophy of the ileal mucosa and neutrophil-poor, monocyte/ macrophage-rich mucosal infiltrates.…”
mentioning
confidence: 99%